Analisis Pengaruh Peran Dewan dan Tanggung Jawab Sosial Perusahaan terhadap Kinerja Perusahaan yang Tercatat di BEI - Meily Juliani; Naida Aisyah Alima (Wahana Riset Akuntansi, 2022)
The purpose of this study is to empirically examine the effect of corporate boards and corporate social responsibility on company performance. The sample data used are 52 company names and meet the predetermined characteristics, namely companies that have sustainability reports with the GRI index totaling 91 items and have been listed on the Indonesia Stock Exchange (IDX) for 5 years, from 2017 to 2021. The research method is using the purposive sampling method with SPSS and Eviews 10 application programs. Based on the findings of the observational data, it was found that the diversity of the board of directors and leverage had a significant negative effect on company performance through ROA and EPS measurements. In addition, the size of the board of directors also has a significant negative relationship with company performance through ROE measurement. Then, for other variables such as corporate social responsibility (CSR), company board size, company board independence and company size have the same effect, namely there is no significant effect on company performance.Keywords: Corporate Board, Corporate Social Responbility, Firm Performance